Educating Teenagers in Pagerwesi Village about the Dangers of Online Gambling Under the Guise of Online Games - Andi Mulyanti Suhartini; Frestina Bhakti Herwidyaningtyas (LPPM ISTeK ICsada Bojonegoro, 2026)
One recent phenomenon is the rise in online gambling practices disguised as online games, particularly those targeting teenagers. In these games, activities that appear to be ordinary play actually involve betting systems, purchasing items with real money, and even cashable prizes, thus containing elements of gambling. Easy access, a variety of engaging games, and the promise of financial gain have drawn many people to online gambling activities, which have serious negative impacts on both individual lives and society as a whole. In Pagerwesi Village, where the majority of the population are families with varying economic and educational backgrounds, supervision of adolescents' digital activities tends to be weak. Many parents don't understand the risks of unsupervised device use, giving their children excessive freedom to access various types of digital games. Therefore, education and outreach regarding the dangers of online gambling hidden within online games are necessary for both adolescents and parents, so they develop digital literacy and awareness of the potential risks. This community service program aims to provide comprehensive education to adolescents and parents in Pagerwesi Village regarding forms of online gambling disguised as games, their negative impacts, and prevention and monitoring strategies that can be implemented independently within the family and school environment. The results of the activity indicate increased awareness among adolescents and the community regarding the importance of understanding the dangers of online gambling disguised as online games for youth in Pagerwesi Village after the education program. For the program to continue, a more inclusive approach and increased digital literacy among the community are needed.